ANALYSIS OF FACTORS AFFECTING THE SUCCESS OF MICRO SMALL AND MEDIUM ENTERPRISES (CASE STUDY OF NAGOYA SHOP IN LHOKSEUMAWE CITY) - Rusydi Abubakar; Rizka Imelia Salsabila; Siti Nurhaliza; Khaira Ummaya; Anisa Br Pelawi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research aims to analyze the profits of the "Nagoya" shop business so that we can know in detail the amount of profit each month earned by the "Nagoya" shop business in the culinary area on reservoir road in Lhokseumawe City. The data used in this research is primary data obtained by conducting direct interviews with business owners using a list of questions, and secondary data obtained from literature studies in the form of literature, written sources or documents that are relevant to this research. The data analysis method used is descriptive analysis, using business profit analysis, then continued with Return of Cost Ratio analysis, then presented in table form. The results of this research show that the "Nagoya" shop business provides a monthly profit of IDR.7,970,000 with an R/C ratio of 2.35. This shows that every Rp. 1 production cost incurred by a cof ee shop business owner can provide a return in the form of receipts of IDR. 2.35. Where the total revenue is still greater than the total production costs and this business experiences profits Every